Prognostic value of inflammatory biomarkers in aged patients with oral squamous cell carcinoma - Yoshimura, Takuya; Suzuki, Hajime; Takayama, Hirotaka; Higashi, Shotaro; Hirano, Yuka; Tezuka, Masahiro; Ishida, Takayuki; Ishihata, Kiyohide; Amitani, Marie; Amitani, Haruka; Nishi, Yasuhiro; Nakamura, Yasunori; et al. (Frontiers in Pharmacology, 2022)
Background: It is clinically important to develop better prognostic biomarkers for oral squamous cell carcinoma (OSCC), especially within the scope of clinically and routinely performed tests, to guide appropriate clinical treatment and follow-up. In this study, we retrospectively investigated which of the multiple inflammation-nutrition markers are useful in predicting the prognosis of patients with OSCC. Methods: The preoperative neutrophil-lymphocyte ratio (NLR), lymphocyte–monocyte ratio (LMR), platelet–lymphocyte ratio (PLR), CRP-albumin ratio (CAR), Glasgow prognostic score (GPS), modified GPS (mGPS), prognostic nutritional index (PNI), controlling nutrition status (CONUT), and modified CONUT (mCONUT) were retrospectively evaluated using blood samples collected 1 to 5 days before surgery. To estimate the effect on the prognosis of tumor progression, the mean values of the markers between stages I/II and III/IV were used for subgroup analysis. The multivariate Cox proportional hazards model included all independent variables significantly associated with survival in the univariate analysis to determine the independent variables. Results: A total of 112 patients (69 males and 43 females) with primary OSCC who underwent surgical treatment at our hospital were included. There were statistically significant differences in the mean values of monocytes, platelets, and albumin between stages I/II and III/IV. According to the multivariate Cox proportional hazards regression, a low PNI was associated with shorter overall survival (OS) and disease-free survival (DFS); women were associated with shorter DFS. Conclusion: The pretreatment PNI showed outstanding prognostic value in 5-year OS and DFS for patients with OSCC. Future extensive prospective studies in a large sample are warranted to validate our results in patients with OSCC